Migrating workers and jobs: a challenge to the European social model? - Simon Commander; Axel Heitmüller; Laura Tyson (Institute for the Study of Labor (IZA), 2006)
This paper proceeds from two key assumptions. The first is that European countries are likely to face increased immigration of individuals. The second is that the emigration of jobs from Europe to other regions of the world through offshoring is also likely to increase. It has been widely argued that both factors are contributing to growing insecurity among European workers. This paper has two goals: first, to put the wider discussion of job displacement and wage changes resulting from immigration and offshoring on a firmer empirical foundation; and second, to explore changes in the European social model that will allow the European economies to adjust to the challenges and respond to the opportunities resulting from increased global competition from emerging market economies. Both immigration and offshoring confront European policy makers with trade-offs between efficiency and equity. These tradeoffs can be eased by active labour market and education policies to enhance the flexibility and skills of European workers so that they enjoy the productivity advantages necessary to support high wages and compete in the global economy. Such policies must combine an appropriate balance of incentives, obligations and benefits that focus on the overall employability of workers rather than on the number of jobs in a particular company or sector. A key challenge in designing such policies is how to combine generous income support for jobseekers while at the same time strengthening their incentives to find and accept available jobs.
Keywords: J3; J6; H2; L0; 330; offshoring; migration; social model; displacement